ANALYSIS OF DELAYS IN COAL DELIVERY ACTIVITIES AT PT PILAR PUTRA MAHAKAM - Purnomo , Budi; Octavitri , Yollanda; Nur Bintari, Pramudyasari; Aisyah Wiliz, Moudyna (Yayasan Education and Social Center, 2025)
One of the shipping activities frequently carried out in the Indonesian shipping industry is coal shipping. Indonesia is one of the world's leading coal mining countries, and the island of Kalimantan is the largest coal producer in Indonesia. Kalimantan Island is one of Indonesia's mining production areas. One of the shipping activities frequently carried out in the Indonesian shipping industry is coal shipping. PT Pilar Putra Mahakam participates in supporting the timely delivery of coal from Senyiur to the North Sulawesi 1 Steam Power Plant. The purpose of this study was to determine the factors causing delays in coal deliveries by the Tugboat Nunukan 1. This study was conducted at PT Pilar Putra Mahakam from August 1, 2024, to July 31, 2025. This study used a descriptive qualitative method with data collection techniques of observation, interviews, and documentation. Data were sourced from primary and secondary sources. The results of this study explain the factors influencing delays in coal deliveries by the Tugboat Nunukan 1 from Senyiur Jetty to PLTU 1, including technical damage to the vessel, inaccurate surveyors during the ship's seaworthiness survey before chartering, and traffic congestion.